دراسة تاثير اختلاف درجة الحرارة على بعض الخصائص الميكانيكية والحرارية لمتراكب من البولي اثيمين عالي الكثافة المدعم بألياف الزجاج - صاحب, مزهر علي (Al-Nahrain Journal of Science, 2012)
The project involved the preparation of composite material of high density polyethylene (HPE) reinforced with (28%) ratio of glass fiber. The rein forcement materials were chopped strand mat. For purpose, a single – screw extruder is used in test – sample preparation, followed by use the hot – press several plates extruded along opposite direction. A comparison is made between the properties (Elastic modulus (E), surface indentection, impact strength and thermal conductivity) of the composites with those of unreinforced high density polyethylene to find out the effect of reinforcement on the compositesat varying temperatures (20,30,50 ).It was found that elastic modulus for (HPE) increases when the material reinforced with fibers, where material hardness with reinforcement increases where as it decreases when temperature increases.Impact strength and thermal conductivity increases with reinforcement and temperature rise.